Patient-Oriented pharmacy education - Mesut Sancar (İstanbul Journal of Pharmacy)
The pharmacy profession has evolved from a traditional role to patient-oriented practices in the last 60 years, and the concepts of clinical pharmacy and pharmaceutical care have begun to be mentioned more frequently. In parallel with these developments, pharmacy faculties have started to change their existing curricula in line with the philosophy of pharmaceutical care. For this purpose, more importance has begun to be given to experiential programs. One of the most important requirements for clinical pharmacy and pharmaceutical care education is clinical rounds. The benefits of training performed in a clinic in the field of pharmacy are quite high. It is relatively more difficult to evaluate students in real environments, such as clinics, and more emphasis should be placed on evaluating student performance in practice environments. According to the American Council on Pharmacy Education (ACPE), clinical assessment should be able to measure cognitive learning, mastery of basic practice skills, and the ability to use data when solving real problems. It is essential to switch to structured skill-based training in pharmacy departments and adopt a problem- and task-based education approach. The pharmacy profession, which has made valuable contributions to public health from the past to the present, will continue to be an indispensable part of the healthcare system in the future, with updates to be made in education models in line with the needs of the new era.